Social Media Habits on Students and Teacher Development - Pribadi, Irsyad Afif; Zulaikha, Siti; Delina, Mutia (International Journal of Science and Society, 2025)
The internet poses significant risks to students whose cognitive development is still ongoing. These risks include negative impacts such as low literacy levels, exposure to pornography, instant gratification mindset, apathy, cybercrime, and cyberbullying. This study aims to cultivate positive behavioral habits and encourage teachers to create educational content on social media. Promoting positive behavior on social media is the primary focus of this research. Furthermore, building collaboration and elaboration between students and teachers in developing educational content on social media will enhance the school’s reputation. This study employs quantitative methods, utilizing variables such as social media, teachers' self-directed learning, and teachers' personal development. The respondents consist of 150 individuals aged between 23 and 35. Data collection was conducted using questionnaires, and the data were analyzed through linear regression and path analysis. The findings indicate a positive influence of social media and self-directed learning on teachers' personal development, with a total contribution of 63.47%, as demonstrated by path analysis. The path analysis calculations suggest these three variables have a strong influence and significant relationship.